A GUIDEBOOK ON HOW TO BE STUDENTS IN AN AMERICAN UNIVERSITY FOR STUDENTS OF ALFALINK OVERSEAS STUDY AND ENGLISH COURSE - Diana Natalia Tanusaputra; Jusuf I Ibrahim (Institute of Research and Community Outreach - Petra Christian University, 2016)
In the internship program, I worked at West Alfalink which is located at Ruko Rich Palace kav. I-1 Jl. MayjenSungkono 149-151. Alfalink is an overseas education consultant / agent and English language center. In this company, I found three problems. One of them is no guidebook for students who choose the USA to do their overseas study. By looking at this condition, I decided to make the USA guidebook for Alfalink’s students. It can be an effective tool for the company to give detailed information for the students. By providing this guidebook, Alfalink and students can get a lot of benefits. First, Alfalink’s staff do not need to give long explanation to the students and to new staff. Second, Alfalink can use it as a promotional tool. Last, students can get complete information about the USA.